Customer's perception towards merchandise presentation of men department at Mun Loong, Hankyu Jaya , Bangsar / Ratno Affendi Kamarudin - Kamarudin, Ratno Affendi (Faculty of Business and Management, 1998)
Consumer shopping behavior such as the choice of store is influenced by their perceptions of those stores. Perception is a complex process by which people select, organize and interpret sensory stimulation into a meaningful picture of the world. An understanding of consumer perceptions is important to the retailer as a customer's decision to made a purchasing on merchandising will be influenced to a large extent by the way he perceives the product. His perceptions will not affect on their quality, style and design but also by the attributes which the successful retailer is able to lead a product through display, pricing and other tools of support The purpose of project paper, is to study about how the customer perceive this department towards the display, variety , store atmosphere, staff and merchandise presentations.